Investigation of bearing failures using vibration analysis - Tóth, Dániel (Design of Machines and Structures, 2024)
Bearings are important components of most machinery and their working con-ditions influence the operation of the entire machinery. Even if bearings are being used under excellent conditions, sooner or later material fatigue will occur. Besides other things poor operating environment contaminated or peculiarly moist areas and improper handling practices cause premature failures. This article focuses on vibration analysis methods for detecting bearing failures and presents a special lifetime test procedure.